Profil Antropometri Atlet Berdasarkan Prinsip Keberbakatan Di SSB Kabupaten Labuhan Batu - Nugraha, Harly; Hasibuan, Sanusi; Supriadi, Amir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine and obtain anthropometric data of SSB athletes in Labuhan Batu Regency. The problem in this study is based on the results of observations and observations that have been made to place athletes in SSB Bintara Utara and Buana Putra only based on ability (skill) in football games not by doing anthropometric tests first so that there are still some athletes whose height and weight are not ideal in placing positions in SSB. ents. The population amounted to 101 people and the sample in this study amounted to 30 athletes with samples using purposive sampling techniques. The data analysis technique is BMI measurement. The results of the research obtained then the Anthropometric Profile of Athletes in SSB Labuhan Batu Regency can be declared normal with a normal weight category with a total of 19.21 which in the norm is in the normal weight category. This was decided based on the results obtained from the norm of 15 people entering the underweight category, 13 people entering the normal weight category, 0 people entering the overweight category, 0 people entering the pre-obesity category, 1 person entering the obesity category I, and 1 person entering the obesity II category.in conclusion, must be improved in an effort to optimize athletes in playing football. Keywords : Anthropometric Profile, Principle of Giftedness, Football school